LTE small cell optimization : 3GPP evolution to release 13 - Holma, Harri, 1970-; Toskala, Antti; Reunanen, Jussi (Hoboken : John Wiley & Sons, Inc., 2015)
'This book addresses R&D and standardization activities on LTE small cells and network optimization, focusing on 3GPP evolution to Release 13. In addition, the book is written by experts from Renesas, T-Mobile, Teliasonera and Videotron. The book covers: 1) LTE small cells from specification to products and field results, 2) Latest 3GPP evolution to Release 13 and 3) LTE optimization and learnings from the field'--
Includes bibliographical references and index.
Keywords: Long-Term Evolution (Telecommunications).